Activity measurements and determination of nuclear decay data of 166Ho in the MRTDosimetry project - Bobin, C; Bouchard, J; Chisté, V; Collins, S M; Dryák, P; Fenwick, A; Keightley, J; Lépy, M-C; Lourenço, V; Robinson, A P; Sochorová, J; Šolc, J; et al. (Applied radiation and isotopes, 2019)
Holmium-166 is a high-energy β--emitter radionuclide (~ 1.8 MeV) with a short half-life (~26.8h) that offers great potential as an alternative to 90Y for the treatment of liver cancer based on radioembolization. The possibility of quantitative Single Photon Emission Computed Tomography (SPECT) imaging of the main γ-ray emission at 80.6 keV, in addition to strong paramagnetic properties suitable for Magnetic Resonance Imaging (MRI), complement this therapeutic potential. The present paper describes the measurements carried out in three European radionuclide metrology laboratories for primary standardization of 166Ho and new determinations of X- and γ-ray photon-emission intensities in the framework of the European EMPIR project MRTDosimetry. New half-life measurements were also performed.
Keywords: radionuklidy; dávka záření; Half-life measurements; Molecular radiotherapy; Liver Neoplasms; Ho-166; Tomography, Emission-Computed, Single-Photon; holmium; Activity standardization; lidé; Holmium; nádory jater; Humans; MRTDosimetry project; Radioisotopes; jednofotonová emisní výpočetní tomografie; γ-spectrometry; Radiation Dosage